The promise of blockchain: analysing potentials and barriers in supply chain management - Sinniati, Sinniati; Darma, Gede Sri (BISMA (Bisnis dan Manajemen), 2023)
This study explored the potential and barriers to implementing blockchain technology in Supply Chain Management (SCM). The purpose of the research was to determine the potential of implementing blockchain technology to enhance SCM performance, identify the challenges faced in implementing blockchain in SCM, and understand the constraints and obstacles that need to be overcome for successful implementation. The research method applied was a Systematic Literature Review (SLR) using the PRISMA protocol and the PICOC framework, with 73 papers collected from 2018 to June 2023. The study identified blockchain's potential to revolutionise SCM by enhancing traceability, transparency, efficiency, trust, and security. It also found that blockchain could support sustainability and anti-counterfeiting efforts. However, significant barriers exist, including technological challenges like immaturity, complexity, and scalability issues, as well as organisational and environmental hurdles such as lack of knowledge, high costs, and insufficient government regulation. To fully realise blockchain's benefits in SCM, stakeholders must address these barriers through targeted investments, fostering industry-wide collaboration, and establishing clear regulatory frameworks.